Development of a Basic Sepak Sila Training Model in Sepak Takraw for Fifth-Grade Elementary Students - Gunawan, Gunawan; Humaedi, Humaedi; Fathurahim, Fathurahim; Sri Rejeki, Hendriana (UNIB Press, 2025)
Sepak sila, as the most dominant technique in sepak takraw, requires a training model tailored to player characteristics. Therefore, it is essential to develop a training model that meets these needs. This study aims to describe the feasibility, practicality, and effectiveness of the sepak sila basic technique training model in sepak takraw for fifth-grade elementary school students. The research method used is Research and Development (R&D) with the ADDIE development model. The study's subjects were fifth-grade students from SDN Taipa, with trials involving one teacher and 28 students. The results indicate that the development of the sepak sila basic technique training model in sepak takraw is feasible, with a validity score of 91.27% in the